2019
DOI: 10.1038/s42003-019-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle microRNA quantification from plasma using an integrated microfluidic device

Abstract: Extracellular vesicles (EV) containing microRNAs (miRNAs) have tremendous potential as biomarkers for the early detection of disease. Here, we present a simple and rapid PCR-free integrated microfluidics platform capable of absolute quantification (<10% uncertainty) of both free-floating miRNAs and EV-miRNAs in plasma with 1 pM detection sensitivity. The assay time is only 30 minutes as opposed to 13 h and requires only ~20 μL of sample as oppose to 1 mL for conventional RT-qPCR techniques. The platform integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 42 publications
0
104
1
Order By: Relevance
“…MicroRNAs (miRNAs) are small, approximately 22-nucleotide long strands of small non-coding RNAs that regulate posttranscriptional processes (Ramshani et al, 2019;Rios et al, 2019). Unlike RNA, miRNAs show high stability in fluids and can be reliably detected in the blood (Mitchell et al, 2008).…”
Section: Mvs Micrornas Mediate Ckd-associated Cvdsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are small, approximately 22-nucleotide long strands of small non-coding RNAs that regulate posttranscriptional processes (Ramshani et al, 2019;Rios et al, 2019). Unlike RNA, miRNAs show high stability in fluids and can be reliably detected in the blood (Mitchell et al, 2008).…”
Section: Mvs Micrornas Mediate Ckd-associated Cvdsmentioning
confidence: 99%
“…MiRNAs levels differ in healthy and diseased tissues and play a critical role in the maintenance of cardiovascular homeostasis (Pfeifer et al, 2015). EV-associated miRNAs have been studied extensively Ramshani et al, 2019). Numerous studies have shown that miRNAs can be used as valuable pathological and therapeutic biomarkers in both cells and EVs (Bekris and Leverenz, 2015;Lei et al, 2017).…”
Section: Mvs Micrornas Mediate Ckd-associated Cvdsmentioning
confidence: 99%
“…An innovative chemical-free exosome lysing system, coupled with membrane sensing, was integrated and presented by Ramshani et al [125]. The purpose of this study was to develop a PCR-free diagnostic platform in order to quantify, in a one-step manner, exosome-derived miRNA from untreated plasma samples ( Figure 5D).…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…The chip's detection principle relies on ion-exchange membranes, where the anionic one is functionalized with a complementary probe. The current-voltage interaction throughout the membrane sensor is drastically shifted during hybridization, which can be directly linked to miRNA levels in the sample [125].…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Such a high analyte concentration factor enhances the sensitivity of the sensors by orders of magnitude. For example, we can extend the limit of detection of our membrane sensor for microRNA from nM to pM [35,36] and for our nanoparticle sensors from 40 nM to 500 pM [37]. We shall, however, focus on how they can improve the pretreatment portion of the liquid biopsy platform here.…”
Section: Membrane Microfluidics and Analyte Concentration/purificatiomentioning
confidence: 99%